Réponses

2014-02-23T16:56:01+01:00
Bonjour
7x² -x = 0
x(7x -1) =0
soit x = 0
soit 7x -1 = 0
7x = 1
x = 1/7
solutions : 0 et 1/7

9x² = 3x
9x² -3x = 0
3x( 3x -1) = 0
soit 3x = 0 d'où x = 0
soit 3x -1 = 0
3x = 1
x = 1/3
Solutions : 0 et 1/3
2014-02-23T17:00:23+01:00
 7 x ² – x = 0
x ( 7x - 1) = 0
donc x = 0   ou  7x -1 = 0
                           7x = 1        
                            x = 1/7

b /9 x ² = 3 x
9x² -3x = 0
3x (3x -1) =0
3x =0     ou 3x -1 = 0
x =0/3 = 0    ou 3x = 1
                            x = 1/3